Envelhecimento saudável: o papel da alimentação e nutrição - Ana Sofia Carvalho Marques Pinto (2021)
The increase in average life expectancy has led to an increase in the prevalence of chronic diseases and is a major challenge in terms of developing strategies that allow healthy aging and well-being. Food constitutes one of the fundamental pillars of healthy aging, and it is recognized that the practice of a dietary pattern that approaches the Mediterranean dietary pattern in the long term constitutes protection in that it privileges the intake of anti-inflammatory foods and the reduced intake of pro-food. inflammatory. The consumption of pro-inflammatory foods has been shown to induce an increased risk of developing cancer, cardiovascular diseases and dementia. Although the theoretical plan recognizes the evidence of the protective effect of some foods, more randomized and controlled trials are needed to assess the risk / benefit of food, in larger populations, during longer follow-up. In short, the benefit of the Mediterranean Diet in promoting healthy aging seems to be consensual, especially for its richness and variety, as it is recognized that the synergistic effect of food is greater than its isolated effect.